Numerical analysis of effects of tooth anteversion angle on labyrinth sealing characteristics. (29th June 2019) - Wang, Guoda; Lu, Shaobin; Cheng, Guanbing
Numerical analysis on effects of tooth anteversion angles was made on one straight labyrinth sealing performances. Both labyrinth physical and computational models were established by softwares Solidworks and ANSYS CFX. Five labyrinth tooth anteversion angles were considered. Variations of airflow total pressure and velocity were obtained in one labyrinth with different anteversion angles. The mass flow leakage and its discharge coefficients were calculated accordingly. The simulation results indicate that the pressure degradation becomes more important as the tooth anteversion angle increases. The airflow accelerates across the labyrinth tooth and decelerates in the cavities. The tooth number increases oscillations of flow velocity. The bigger tooth anteversion angle affects the airflow process more early than the smaller ones. With increases of anteversion angles, the labyrinth mass flow leakage and its discharge coefficient decreases firstly and then increases. There is an optimal anteversion angle of the labyrinth regardless the tooth numbers.